Electrode material and electrode composed of wet powder, method for producing the same, and secondary battery having the electrode
By using wet powder in the pendulum state or cable state on the electrode active material layer, and forming a concave and convex structure through pressurization molding, the problem of difficult to increase the surface area of the electrode active material layer in the prior art is solved, and the performance of the secondary battery is improved.
Patent Information
- Application Number
- CN202210086222.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-01-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-01-25
AI Technical Summary
In the prior art, it is difficult to form a sufficient surface area on the electrode active material layer of the secondary battery to increase, and the ductility during pressing molding is poor, making it difficult to accurately form the concave and convexity of the desired depth.
A wet powder consisting of agglomerated particles including electrode active material particles, binder resin and solvent is used to adjust the existence form of the agglomerated particles to form a pendulum state or a cable state, so as to avoid the solvent layer on the surface of the agglomerated particles, and a concave and convex structure is formed by pressurization to increase the surface area.
The surface area of the electrode active material layer is significantly increased, the internal resistance reduction of the secondary battery and the performance of high-rate charging and discharging characteristics are improved, and the surface density and uneven adhesive resin are prevented by controlling the void distribution.
Smart Images

Figure CN114824156B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode for a secondary battery, a method for producing the same, and a secondary battery having the electrode. Specifically, the present invention relates to a method for producing an electrode for a secondary battery using a wet powder in which a gas phase is controlled. Background Art
[0002] Secondary batteries such as lithium-ion secondary batteries have high energy density at a reduced weight and are therefore preferably used as high-output power sources for driving vehicles such as electric vehicles and hybrid vehicles, and demand for them is expected to continue to increase in the future.
[0003] Typical structures of the positive electrode and negative electrode (hereinafter referred to as "electrode" when not specifically distinguishing between positive and negative electrodes) in such a secondary battery include a structure in which an electrode active material layer mainly composed of an electrode active material is formed on one or both surfaces of a foil-shaped electrode collector.
[0004] The above-mentioned electrode active material layer is formed by the following method, that is, dispersing solid components such as electrode active material, binding material (binder), conductive material, etc. in a specified solvent, applying the slurry (paste) electrode composite material (hereinafter referred to as "composite material slurry") prepared in this way to the surface of the collector to form a coating film, and after the coating film is dried, applying pressure to form a specified density and thickness.
[0005] In addition, instead of such film formation based on composite material slurry, wet powder film formation (Moisture Powder Sheeting: MPS) using a so-called wet powder (Moisture Powder) in which the proportion of solid components is higher than that of the composite material slurry and a granular aggregate is formed while the solvent is retained on the surface of the active material particles and the surface of the binder molecules is studied. For example, the following patent documents 1 to 4 describe a method for manufacturing an electrode for a lithium ion secondary battery, characterized in that an active material layer is formed from a wet powder.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-136016
[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-057383
[0010] Patent Document 3: Japanese Patent Application Publication No. 2018-137087
[0011] Patent Document 4: Japanese Patent Application Publication No. 2018-037198 Summary of the invention
[0012] It is expected that the secondary battery used as a high-output power source for driving a vehicle will be further improved in performance. For example, it is required to reduce the internal resistance of the battery, improve the high-rate charge and discharge characteristics, etc. In this regard, if the surface area of the electrode active material layer formed on the surface of the electrode collector can be increased than before, it can become a method to meet the above requirements.
[0013] However, in the film-forming based on composite material slurry in the past, it is difficult to increase the surface area of the electrode active material layer. That is, in the coating composed of slurry, due to the high ratio of the solvent, the flattening (leveling) effect caused by the surface tension after the coating is formed is strong, and it is impossible to form a concave-convex surface on the surface of the electrode active material layer (coating) that can increase the surface area of the electrode active material layer. Of course, the surface of the electrode active material layer after the coating is dried can be mechanically pressed, but for the pressurization after drying, due to poor ductility, it is difficult to repeatedly and accurately form the desired depth of the concave-convex at a predetermined interval (pitch). In addition, the surface layer formed by pressurization is partially densified, which is not preferred from the viewpoint of forming an effective conductive path in the entire active material layer.
[0014] On the other hand, it is also difficult to fully increase the surface area of the electrode active material layer by conventional film formation (MPS) based on wet powders. That is, conventional wet powders are so-called "capillary states" described later in which the liquid phase is continuously formed in the entire powder. In the coating film composed of the wet powder, there is still a lot of solvent on its surface, making it difficult to form a concavoconvexity that can increase the surface area of the electrode active material layer.
[0015] Furthermore, when mechanical pressure is applied to the surface of the electrode active material layer after the coating film is dried, similarly to the film formation using the composite material slurry, it is difficult to accurately form irregularities of a desired depth due to poor ductility.
[0016] Therefore, the present invention is made in view of the above situation, and its purpose is to provide an electrode material (composite material) with good ductility and capable of easily increasing the surface area of the electrode active material layer in the coating stage before drying by press molding, as well as to provide an electrode for a secondary battery and a method for manufacturing the same that achieves an increase in surface area by using the electrode material.
[0017] In order to achieve the above-mentioned object, the present inventors have studied the content of MPS and the properties of wet powders used in the MPS so far. Although the wet powders so far have a higher solid content than the composite material slurry (paste), it is noted that the solid components and the solvent of the agglomerated particles constituting the powder are in a relatively capillary state, that is, a relatively large amount of solvent is tightly bound inside the agglomerated particles constituting the wet powder, and a solvent layer is also formed on the surface of the agglomerated particles. In addition, it is noted that no research has been conducted on the gas phase, that is, the existence form of the voids in the agglomerated particles.
[0018] Therefore, unlike conventional wet powders, the solid component (solid phase), solvent (liquid phase) and voids (gas phase) exist in the form of a pendulum state or a cord state (cord I state) close to a pendulum state as described later. In other words, an appropriate amount of solvent (liquid phase) is present in the agglomerated particles constituting the powder, which is neither too much nor too little for bridging the electrode active material particles that will form the agglomerated particles. Furthermore, voids that are connected to the outside are formed in the agglomerated particles, and formation of a substantial solvent layer on the surface of the agglomerated particles is avoided. This allows the desired bumps and depressions to be formed on the coating film before drying formed on the collector by press molding, etc., and the surface area of the electrode active material layer can be easily increased, thereby completing the present invention.
[0019] That is, the wet powder disclosed herein for forming an electrode active material layer on an electrode current collector of either the positive or negative electrode is a wet powder composed of aggregated particles containing a plurality of electrode active material particles, a binder resin, and a solvent.
[0020] Furthermore, the wet powder disclosed herein is characterized in that at least 50% by number (more preferably 70% by number, and particularly 80% by number) of the above-mentioned agglomerated particles constituting the powder have the following properties:
[0021] (1) The solid, liquid and gas phases form a pendulum state or a cable-belt state, and
[0022] (2) The solvent layer is not visible on the outer surface of the aggregated particles under electron microscope observation.
[0023] As described above, the wet powder composed of the agglomerated particles in the pendulum state or the rope state is controlled in such a way that the solvent (liquid phase) is kept in a bridging state between the electrode active material particles and between the electrode active material particles and the binder resin, and at the same time, the gas phase forms gaps (connected pores) in the agglomerated particles that are connected to the outside.
[0024] Therefore, if the wet powder disclosed herein is used to form a coating film on a current collector before drying, a desired concavoconvex structure can be formed on the surface of the coating film by press molding or the like, and the surface area per unit area of the electrode active material layer can be easily increased.
[0025] In addition, due to the presence of the solvent liquid bridge, when the dried electrode active material layer is compressed to a specified thickness, only the surface layer of the electrode active material layer can be prevented from being partially densified. In addition, due to the presence of the interconnected pores, the solvent does not contact the surface of the processing tool during pressure molding, and the pores are used as vents during demolding of the coating film, thereby achieving demolding.
[0026] Furthermore, unlike a coating composed of a slurry or a wet powder in a capillary state, since the free movement of the solvent in the coating formed on the electrode collector is restricted, it is possible to prevent the binder resin from being unevenly distributed in the coating during the drying process.
[0027] In a preferred embodiment of the wet powder for forming an electrode active material layer disclosed herein,
[0028] The bulk density obtained by measuring the wet powder (g) by placing it into a container of a specified volume (mL) in a manner of flattening without applying any force is set as loose bulk density X (g / mL), and the density calculated from the composition of the wet powder assuming that there is no gas phase is set as true density Y (g / mL), and the ratio Y / X of the true density Y to the loose bulk density X is 1.2 or more.
[0029] In addition, in a further preferred embodiment of the wet powder, the following state is achieved: when a coating with a film thickness of 300 μm to 1000 μm is formed on an electrode collector by the wet powder and pressurized at a pressure of 60 MPa, the gas residual rate in the coating after pressurization (i.e., (volume of air / volume of coating) × 100) is less than 10 vol%.
[0030] In a further preferred embodiment of the wet powder, the following state is achieved: in the void distribution obtained by void observation of the above-mentioned pressurized coating film by radiation X-ray tomography, 2000 μm with respect to the total void volume (100 vol%) 3 The void ratio of the above volume is 30 vol% or less.
[0031] If the wet powder has a structure that can achieve these characteristics, it is possible to form an electrode active material layer having more excellent conductive paths, charge carrier (eg, lithium ion) paths, and void paths.
[0032] In addition, in order to achieve the above-mentioned object, any one of the positive and negative electrodes of the secondary battery disclosed herein comprises an electrode collector and an electrode active material layer formed on the collector. Furthermore, the electrode is characterized in that the average surface area of the reference area represented by Lcm×Bcm (L, B are integers of 3 or more) in the electrode active material layer is 1.05×L×B cm when the surface area is measured at n different points (n is an integer of 5 or more) from each other. 2 above.
[0033] The wet powder disclosed herein can achieve 1.05×L×B cm 2 The surface area of the electrode active material layer is increased as described above.
[0034] In a preferred embodiment of the secondary battery electrode disclosed herein, a gas residual ratio ((volume of air / volume of coating film)×100) in the electrode active material layer is 10 vol% or less.
[0035] In a further preferred embodiment of the secondary battery electrode, in the void distribution obtained by void observation of the electrode active material layer by radiation X-ray tomography, 2000 μm of the total void volume (100 vol%) is 3 The void ratio of the above volume is 30 vol% or less.
[0036] An electrode having these characteristics can realize an electrode active material layer having a more excellent conductive path, and can contribute particularly to improving the performance of secondary batteries used as a power source for driving vehicles.
[0037] In a further preferred embodiment of an electrode for a secondary battery, the electrode active material layer is equally divided into two layers, an upper layer and a lower layer, in the thickness direction from the surface of the active material layer to the collector, and when the concentrations (mg / L) of the binder resin in the upper layer and the lower layer are set to C1 and C2, respectively, the relationship of 0.8≤(C1 / C2)≤1.2 is achieved.
[0038] By forming an electrode active material layer using the wet powder disclosed herein, it is possible to suppress the occurrence of unevenness of the binder resin during the drying process, and thus it is possible to form an electrode active material layer having a uniform composition as a whole.
[0039] In addition, as another aspect of the present invention for achieving the above-mentioned object, a method for producing an electrode having an electrode current collector of either a positive electrode or a negative electrode and an electrode active material layer is provided.
[0040] That is, the electrode manufacturing method disclosed herein includes the following steps:
[0041] A step of preparing a wet powder, wherein the wet powder is composed of agglomerated particles including a plurality of electrode active material particles, a binder resin and a solvent, wherein at least 50% of the agglomerated particles have the following properties:
[0042] (1) The solid, liquid and gas phases form a pendulum state or a cable-like state, and
[0043] (2) No layer of the solvent is visible on the outer surface of the aggregated particles under electron microscope observation;
[0044] a step of applying the wet powder onto the current collector to form a coating film composed of the wet powder; and
[0045] A step of subjecting the surface of the coating film to a treatment for forming irregularities to form an electrode active material layer having irregularities formed on the surface in a predetermined pattern.
[0046] According to the electrode manufacturing method having the above-described structure, a preferred secondary battery electrode having the above-described characteristics can be provided.
[0047] In a preferred embodiment of the electrode manufacturing method disclosed herein, the above-mentioned concavo-convex forming treatment is performed in a manner to form a concavo-convex surface in which the average surface area of the reference area represented by Lcm×Bcm (L and B are integers of 3 or more) in the electrode active material layer is measured at n different points (n is an integer of 5 or more) is 1.05×L×B cm 2 above.
[0048] According to the preferred embodiment of the electrode manufacturing method disclosed herein, it is possible to provide an electrode having a thickness of 1.05×L×B cm 2 The secondary battery electrode has the above-mentioned increased surface area of the electrode active material layer.
[0049] In another preferred embodiment of the electrode manufacturing method disclosed herein, the coating film forming step is performed as follows:
[0050] The wet powder is supplied between a pair of rotating rollers to form a coating film composed of the wet powder on the surface of one rotating roller.
[0051] Thereafter, the coating film is transferred onto the surface of the current collector conveyed on another rotating roll.
[0052] The coating film composed of the wet powder disclosed herein has excellent ductility because the aggregated particles constituting the powder exist in the following form. Thus, a preferred electrode active material layer can be formed by so-called roll film formation.
[0053] (1) The solid, liquid and gas phases form a pendulum state or a cable-belt state, and
[0054] (2) The solvent layer is not visible on the outer surface of the aggregated particles under electron microscope observation.
[0055] Therefore, as a preferred embodiment, there is a method in which the above-mentioned unevenness forming treatment is performed by bringing a rotating roller having a predetermined unevenness pattern formed on its surface into contact with the surface of the coating film of the current collector having the above-mentioned coating film.
[0056] In addition, according to the present application, there is provided a secondary battery including positive and negative electrodes, wherein at least one of the positive and negative electrodes includes an electrode of any of the aspects disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 The diagrams schematically show the existence forms of the solid phase (solid components such as active material particles), liquid phase (solvent), and gas phase (voids) in the agglomerated particles constituting the wet powder, wherein (A) represents the pendulum state, (B) represents the rope state, (C) represents the capillary state, and (D) represents the slurry state.
[0058] Figure 2 This is an explanatory diagram schematically showing an example of a stirring granulator for producing the wet powder disclosed herein.
[0059] Figure 3 This is a flowchart showing a schematic process of an electrode manufacturing method according to one embodiment.
[0060] Figure 4 It is an explanatory diagram schematically showing the structure of a roll-type film-forming apparatus according to one embodiment.
[0061] Figure 5 It is a block diagram schematically showing the configuration of an electrode manufacturing apparatus including a roll-type film-forming unit according to one embodiment.
[0062] Figure 6 It is an explanatory diagram schematically showing the different degrees of concave-convex shapes that can be formed on the surface of a coating (electrode active material layer) depending on the material used or the state. (A) shows the case of a coating formed by a composite material slurry (paste), (B) shows the case of a coating formed by a conventional wet powder, (C) shows the case of a coating formed by the wet powder disclosed herein, and (D) shows the case of an electrode active material layer after the coating formed by the composite material slurry (paste) is dried.
[0063] Fig. 7A This is a surface SEM image showing the structure of a negative electrode active material layer (before pressurization) formed using a conventional solvent-rich wet powder.
[0064] Figure 7BThis is a cross-sectional SEM image showing the structure of a negative electrode active material layer (before pressurization) formed using a conventional solvent-rich wet powder.
[0065] Fig. 8A This is a surface SEM image showing the structure of a negative electrode active material layer (before pressurization) formed using the vapor-phase controlled wet powder disclosed herein.
[0066] Figure 8B This is a cross-sectional SEM image showing the structure of a negative electrode active material layer (before pressurization) formed using the vapor-phase controlled wet powder disclosed herein.
[0067] Fig. 9A The figure shows a three-dimensional image of the void structure observed by X-ray tomography of a negative electrode active material layer (negative electrode active material layer after being pressurized at 60 MPa and before being dried) formed using a conventional solvent-rich wet powder.
[0068] Fig. 9B A three-dimensional image showing the void structure observed by X-ray tomography of a negative electrode active material layer (negative electrode active material layer after pressurization at 60 MPa and before drying) formed using the vapor-phase controlled wet powder disclosed herein.
[0069] Fig. 10A This is a graph showing the distribution of void volumes calculated by three-dimensional image analysis of the void structure observed by X-ray tomography of a negative electrode active material layer formed using conventional solvent-rich wet powder (negative electrode active material layer after pressurization at 60 MPa and before drying). The horizontal axis is the void size (μm 3 ), the vertical axis is the volume fraction.
[0070] Fig. 10B This is a graph showing the distribution of void volumes calculated by three-dimensional image analysis of the void structure observed by X-ray tomography of a negative electrode active material layer (negative electrode active material layer after pressurization at 60 MPa and before drying) formed using the gas phase controlled wet powder disclosed herein. The horizontal axis is the void size (μm 3 ), the vertical axis is the volume fraction.
[0071] Fig.11 This is a cross-sectional SEM-EDX image of a positive electrode active material layer used for F mapping showing the distribution of a binder resin (PVDF) present in a positive electrode active material layer formed using the vapor phase controlled wet powder disclosed herein.
[0072] Fig.12 It is an explanatory diagram schematically showing a lithium ion secondary battery according to one embodiment.
[0073] Explanation of symbols
[0074] 1 Agglomerated particles
[0075] 2 Active material particles (solid phase)
[0076] 3 Solvent (liquid phase)
[0077] 4 Void (gas phase)
[0078] 10 Mixing Granulator
[0079] 20 Roller film forming device
[0080] 31. Electrode collector
[0081] 32 Wet powder (electrode composite material)
[0082] 33 Coating
[0083] 70 Electrode manufacturing device
[0084] 40 Film forming unit
[0085] 50 Coating processing unit
[0086] 60 Drying unit
[0087] 80 Wound electrode body
[0088] 100 Lithium-ion secondary battery DETAILED DESCRIPTION
[0089] Hereinafter, the wet powder disclosed herein and the film forming process (MPS) using the wet powder will be described in detail by taking an electrode preferably used in a lithium ion secondary battery as an example of a typical example of a secondary battery.
[0090] Matters other than those specifically mentioned in this specification and necessary for implementation can be understood as design matters of those skilled in the art based on the prior art in this field. The technical contents disclosed herein can be implemented based on the contents disclosed in this specification and the technical common sense in this field.
[0091] In addition, when a numerical range is described as A to B (where A and B are arbitrary numerical values) in this specification, it means greater than A and less than B (including a range greater than A and less than B) as generally interpreted.
[0092] In this specification, "lithium ion secondary battery" refers to a secondary battery in which lithium ions in an electrolyte carry charge and move. In addition, "electrode body" refers to a structure that is the main body of a battery composed of a positive electrode and a negative electrode. In this specification, when there is no need to specifically distinguish between the positive electrode and the negative electrode, they are abbreviated as electrodes. Electrode active material (i.e., positive electrode active material or negative electrode active material) refers to a compound that can reversibly absorb and release chemical substances (lithium ions in lithium ion secondary batteries) as charge carriers.
[0093] The morphological classification of wet powders is described in "Particle Size Enlargement" by Capes CE (Elsevier Scientific Publishing Company, 1980), and the present specification also adopts the four currently known classifications, and the wet powders disclosed herein are clearly defined. Specifically, they are as follows.
[0094] The existence forms (filling states) of the solid components (solid phase), solvent (liquid phase) and voids (gas phase) in the agglomerated particles that constitute the wet powder can be classified into four types: "pendulum state", "ribbon state", "capillary state" and "slurry state".
[0095] Here the "pendulum state" is like Figure 1 As shown in (A), the solvent (liquid phase) 3 is present discontinuously in a manner that bridges the active material particles (solid phase) 2 in the condensed particles 1, and the active material particles (solid phase) 2 can exist in a connected (continuous) state. As shown in the figure, the content of the solvent 3 is relatively low, and as a result, most of the voids (gas phase) 4 present in the condensed particles 1 exist continuously, forming a connecting hole to the outside. Moreover, in the pendulum state, a layer of the solvent that is continuous over the entire outer surface of the condensed particles 1 cannot be seen in electron microscope observation (SEM observation) as a feature.
[0096] In addition, the "cable status" Figure 1 As shown in (B), the solvent content in the condensed particle 1 is relatively high compared to the pendulum, and the solvent (liquid phase) 3 is continuously present around the active material particles (solid phase) 2 in the condensed particle 1. Since the amount of solvent is still small, the active material particles (solid phase) 2 exist in a connected (continuous) state as in the pendulum state. On the other hand, the proportion of connected pores in the voids (gas phase) 4 in the condensed particle 1 that lead to the outside is slightly reduced, and although there is a tendency for the proportion of discontinuous isolated voids to increase, it can be considered that connected pores exist.
[0097] The cord state is a state between the pendulum state and the capillary state, and is divided into a cord I state close to the pendulum state (i.e., the cord state in a state with a relatively small amount of solvent) and a cord II state close to the capillary state (i.e., the cord state in a state with a relatively large amount of solvent). In the cord I state, it still includes a state in which a layer of solvent is not visible on the outer surface of the condensed particles 1 in electron microscopy observation (SEM observation).
[0098] "Capillary state" such as Figure 1 As shown in (C), the solvent content in the agglomerated particles 1 increases, the amount of solvent in the agglomerated particles 1 approaches saturation, and a sufficient amount of solvent 3 continuously exists around the active material particles 2. As a result, the active material particles 2 exist in a discontinuous state. As a result, the voids (gas phase) existing in the agglomerated particles 1 also exist in the form of isolated voids (for example, 80 vol% of the total void volume) due to the increase in the amount of solvent, and the proportion of voids in the agglomerated particles also decreases.
[0099] "Slurry state" such as Figure 1 As shown in (D) in FIG. 1 , the active material particles 2 are already suspended in the solvent 3 and are in a state that cannot be called aggregated particles. There is almost no gas phase.
[0100] The wet powder disclosed herein is a wet powder that (1) forms the above-mentioned pendulum state and cord state (particularly cord I state). It preferably has (2) as a morphological feature, a layer composed of the above-mentioned solvent that is not visible throughout the entire outer surface of the aggregated particles in electron microscope observation (SEM observation).
[0101] Hereinafter, a wet powder having the above-mentioned requirements (1) and (2) disclosed herein will be referred to as a "gas phase controlled wet powder".
[0102] The gas phase controlled wet powder can be manufactured according to the conventional manufacturing process of wet powder in the capillary state. That is, by adjusting the amount of solvent and the combination of solid components (active material particles, binder resin, etc.) in a manner that the proportion of the gas phase is increased compared to the past, specifically, by forming many continuous voids (connecting holes) inside the agglomerated particles that reach the outside, it is possible to manufacture a wet powder as an electrode material (electrode composite material) contained in the above-mentioned pendulum state or cord state (especially cord I state).
[0103] Furthermore, in order to realize a liquid bridge between active materials with a minimum amount of solvent, it is preferred that the surface of the powder material used has an appropriate affinity with the solvent used.
[0104] As the preferred gas-phase controlled wet powder disclosed herein, the following wet powder can be preferably cited: the state of the three phases observed by electron microscope observation is a pendulum state or a cord state (especially cord I state), and the "ratio of true density Y to loose bulk density X: Y / X" calculated from the loose bulk density X (g / mL) and the true density Y (g / mL) of the raw material matrix is 1.2 or more, preferably 1.4 or more (and further 1.6 or more) and preferably 2 or less, wherein the loose bulk density is the actual bulk density obtained by measuring the obtained wet powder by putting it into a container of a specified volume in a manner of scraping it flat without applying force, and the true density Y of the raw material matrix is the density calculated from the composition of the wet powder assuming that there is no gas phase.
[0105] As the material, the same materials as those used in producing conventional composite material slurry (paste) or wet powder can be used without particular limitation.
[0106] As the electrode active material that is the main component of the solid component, a compound having a composition used as a negative electrode active material or a positive electrode active material of a conventional secondary battery (here, a lithium ion secondary battery) can be used. For example, as the negative electrode active material, carbon materials such as graphite, hard carbon, and soft carbon can be cited. In addition, as the positive electrode active material, LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 Lithium transition metal composite oxides such as LiO4, lithium transition metal phosphate compounds such as LiFePO4. The average particle size (D 50 ) is appropriately about 0.1 μm to 50 μm, and preferably about 1 to 20 μm.
[0107] As other solid components, binder resins, conductive materials, etc. can be cited in the same manner as the case of manufacturing conventional composite material slurry (paste) and wet powder. For example, as binder resins, polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), etc. can be cited. Suitable binder resins are adopted according to the solvent used. In addition, as conductive materials, carbon materials such as carbon blacks such as acetylene black (AB) and carbon nanotubes can be cited as preferred examples.
[0108] In addition, when the wet powder (electrode composite material) is used for forming an electrode of a so-called all-solid battery, the solid electrolyte is used as a solid component. There are no particular limitations, and examples thereof include Li2S, P2S5, LiI, LiCl, LiBr, Li2O, SiS2, B2S3, Z m S n (where m and n are positive numbers, Z is Ge, Zn or Ga), Li 10 GeP2S 12 A sulfide solid electrolyte having the following as constituent elements is a preferred example.
[0109] The solvent may be any solvent that can appropriately disperse (dissolve) the binder resin, and preferred examples include water, N-methyl-2-pyrrolidone (NMP), and butyl butyrate.
[0110] The above materials are used for wet granulation to produce the target wet powder. Figure 2 The stirring granulator (agitator such as a planetary mixer) 10 shown in the figure mixes various materials to produce a wet powder (i.e., an aggregate of agglomerated particles). As shown in the figure, the stirring granulator 10 typically includes a cylindrical mixing container 12, a rotating blade 14 accommodated in the mixing container 12, and a motor 18 connected to the rotating blade (also called a paddle) 14 via a rotating shaft 16.
[0111] In the granulation process, among the above-mentioned materials, the materials (solid components) other than the solvent are first pre-mixed and subjected to solvent-free dry dispersion treatment. Thus, each solid component is formed into a highly dispersed state. Thereafter, preferably, a solvent and other liquid components (such as a liquid binder) are added to the mixture in the dispersed state for further mixing. Thus, a wet powder obtained by appropriately mixing each solid component can be produced.
[0112] Specifically, electrode active materials and various additives (binder resin, thickening material, conductive material, etc.) as solid components are added to the mixing container 12 of the stirring granulator 10, and the motor 18 is driven to rotate the rotary blade 14 at a rotation speed of, for example, 2000rpm to 5000rpm for 1 to 60 seconds (for example, 2 to 30 seconds), thereby manufacturing a mixture of each solid component. Then, an appropriate amount of solvent measured in a manner such that the solid component is 70% or more, more preferably 80% or more (for example, 85 to 98%) is added to the mixing container 12, and the stirring granulation process is carried out. Without particular limitation, the rotary blade 14 is further rotated at a rotation speed of, for example, 100rpm to 1000rpm for 1 to 60 seconds (for example, 2 to 30 seconds). Thus, the various materials in the mixing container 12 can be mixed with the solvent to manufacture a granulated body (wet powder) in a wet state. In addition, aggregation of the wet powder can be prevented by further intermittently performing short-term stirring for about 1 to 5 seconds at a rotation speed of about 1000 rpm to 3000 rpm.
[0113] The particle size of the obtained granules can be larger than the width of the gap between a pair of rollers of the roll film forming device described later. When the width of the gap is about 10 μm to 100 μm (e.g., 20 μm to 50 μm), the particle size of the granules can be 50 μm or more (e.g., 100 μm to 300 μm).
[0114] For the gas phase controlled wet powder disclosed herein, the solid phase, liquid phase and gas phase form a pendulum state or a cord state (preferably the cord I state), and the solvent content is so low that no solvent layer can be seen on the outer surface of the agglomerated particles under electron microscope observation (for example, the solvent fraction can be about 2 to 15%, or 3 to 8%). On the contrary, the gas phase portion is relatively large.
[0115] In order to achieve such an existence form, various treatments and operations that can increase the gas phase can be introduced in the above-mentioned granulation manufacturing process. For example, the excess solvent can be evaporated by exposing the granulation to a dry gas (air or inert gas) atmosphere about 10 to 50 degrees higher than room temperature during or after stirring granulation. In addition, in order to promote the formation of agglomerated particles in a pendulum state or a cord I state in a state with a small amount of solvent, a compression granulation with a strong compression effect can be used to make the active material particles and other solid components adhere to each other. For example, a compression granulator can be used that granulates while applying a compressive force between a pair of rollers while supplying the powder raw material from a vertical direction to the rollers.
[0116] Next, a process for producing an electrode by forming a coating film (electrode active material layer) on a long sheet-shaped electrode current collector using the wet powder disclosed herein will be described in detail. Figure 3It is a flowchart showing the general process of the electrode manufacturing method.
[0117] like Figure 3 As shown, the wet powder manufactured in the above process is prepared (S1), and then, the wet powder is supplied to the electrode current collector in a manner to achieve a predetermined thickness using an appropriate film forming device to form a coating (S2). Then, the concave-convex forming treatment described later is performed, and the surface of the coating composed of the wet powder disclosed here is formed with concave-convex (S3). Then, the surface of the coating formed with the concave-convex surface is dried (S4) to form an electrode active material layer.
[0118] As a preferred film forming apparatus for implementing the above film forming, there can be mentioned the following: Figure 4 The roll film forming device 20 schematically shown in FIG. The roll film forming device 20 includes a pair of rotating rollers 21, 22 consisting of a first rotating roller 21 (hereinafter referred to as "supply roller 21") and a second rotating roller 22 (hereinafter referred to as "transfer roller 22"). The outer peripheral surface of the supply roller 21 and the outer peripheral surface of the transfer roller 22 are opposed to each other. The pair of rotating rollers 21, 22 can be as follows Figure 4 Rotate in the opposite direction as indicated by the arrow.
[0119] The supply roller 21 and the transfer roller 22 are separated by a distance corresponding to the desired thickness of the electrode composite material layer (coating film) 33 formed on the long sheet-shaped electrode current collector 31. That is, there is a gap of a predetermined width between the supply roller 21 and the transfer roller 22, and the thickness of the coating film 33 composed of the wet powder (electrode composite material) 32 attached to the surface of the transfer roller 22 can be controlled according to the size of the gap. In addition, by adjusting the size of the gap, it is also possible to adjust the force that compresses the wet powder 32 passing between the supply roller 21 and the transfer roller 22. Therefore, by obtaining a larger gap size, the gas phase of the wet powder 32 (specifically, each condensed particle) manufactured into a pendulum state or a cable state can be maintained.
[0120] The supply roller 21 and the transfer roller 22 are provided with partitions 25 at both ends in the width direction. The partitions 25 hold the wet powder 32 on the supply roller 21 and the transfer roller 22, and at the same time, they play a role in regulating the width of the coating film (electrode active material layer) 33 formed on the electrode collector 31 by the distance between the two partitions 25. The electrode material (wet powder) 32 is supplied between the two partitions 25 by a feed port (not shown) or the like.
[0121] In the film forming device 20 of this embodiment, a support roller 23 is arranged as a third rotating roller adjacent to the transfer roller 22. The support roller 23 plays a role in conveying the electrode collector 31 to the transfer roller 22. Figure 4 Rotate in the opposite direction as indicated by the arrow.
[0122] The supply roller 21, transfer roller 22, and support roller 23 are respectively connected to independent driving devices (motors) not shown in the figure. By slowly increasing the rotation speeds of the supply roller 21, transfer roller 22, and support roller 23 in turn, the wet powder 32 can be conveyed along the transfer roller 22, and the wet powder is transferred from the circumferential surface of the transfer roller 22 to the surface of the electrode collector 31 conveyed by the support roller 23 as a coating 33.
[0123] It should be explained that Figure 4 In the embodiment, the supply roller 21, the transfer roller 22, and the support roller 23 are arranged so that the respective rotation axes are arranged horizontally, but the present invention is not limited thereto. For example, the supply roller 21, the transfer roller 22, and the support roller 23 may be arranged horizontally as described later. Figure 5 The support rollers are arranged at the positions shown (refer to Figure 5 ).
[0124] In addition, there is no particular restriction on the sizes of the supply roller 21, the transfer roller 22, and the support roller 23, and they can be the same as those of the conventional roller-type film-forming apparatus, for example, the diameters can be 50 mm to 500 mm respectively. The diameters of these three rotating rollers 21, 22, and 23 can be the same diameter or different diameters. In addition, the width of the formed coating can also be the same as that of the conventional roller-type film-forming apparatus, and can be appropriately determined according to the width of the electrode collector of the object to be formed with the coating. In addition, the material of the circumferential surface of these rotating rollers 21, 22, and 23 can be the same as that of the rotating rollers in the conventionally known roller-type film-forming apparatus, for example, SUS steel, SUJ steel, etc. can be cited.
[0125] Next, a preferred embodiment of a method for producing a secondary battery electrode using the wet powder disclosed herein will be described with further reference to the drawings. Figure 5 It is an explanatory diagram showing a schematic structure of an electrode manufacturing apparatus 70 including a roll-type film-forming unit according to the present embodiment.
[0126] The electrode manufacturing device 70 of this embodiment generally comprises: a film forming unit 40 for supplying a wet powder 32 onto the surface of a sheet-like current collector 31 conveyed from a supply chamber (not shown) to form a coating 33, a coating processing unit 50 for pressurizing the coating 33 in the thickness direction and performing a surface roughness forming treatment on the coating, and a drying unit 60 for appropriately drying the coating 33 after the surface roughness forming treatment to form an electrode active material layer.
[0127] The film forming unit 40 is similar to the above-mentioned roll film forming device ( Figure 4 ) is similarly provided with a supply roller 41, transfer rollers 42, 43, 44 and a support roller 45 which are respectively connected to independent driving devices (motors) not shown.
[0128] The film forming unit of this embodiment is provided with a plurality of transfer rollers in series as shown in the figure, and in this example, a first transfer roller 42 facing the supply roller 41, a second transfer roller 43 facing the first transfer roller, and a third transfer roller 44 facing the second transfer roller and also facing the support roller 45.
[0129] By adopting such a configuration, the sizes of the gaps G1 to G4 between the rollers can be made different, and an appropriate coating film can be formed while maintaining the communicating holes of the wet powder.
[0130] As shown in the figure, when the first gap G1 is set between the supply roller 41 and the first transfer roller 42, the second gap G2 is set between the first transfer roller 42 and the second transfer roller 43, the third gap G3 is set between the second transfer roller 43 and the third transfer roller 44, and the fourth gap G4 is set between the third transfer roller 44 and the support roller 45, the size of the gap is set in such a way that the first gap G1 is relatively the largest and the second gap G2, the third gap G3, and the fourth gap G4 gradually decrease in sequence (G1>G2>G3>G4). By performing multi-stage roller film formation in which the gap gradually decreases along the conveying direction (travel direction) of the collector 31, a coating film composed of the wet powder 32 can be formed in which the state of the connecting holes is appropriately maintained. That is, the film forming unit 40 of this embodiment can be operated as follows.
[0131] The supply roller 41, the first transfer roller 42, the second transfer roller 43, the third transfer roller 44, and the support roller 45 are connected to independent driving devices (motors) not shown, and can rotate at different rotation speeds. Specifically, the rotation speed of the first transfer roller 42 is faster than the rotation speed of the supply roller 41, the rotation speed of the second transfer roller 43 is faster than the rotation speed of the first transfer roller 42, the rotation speed of the third transfer roller 44 is faster than the rotation speed of the second transfer roller 43, and the rotation speed of the support roller 45 is faster than the rotation speed of the third transfer roller 44.
[0132] By gradually increasing the rotation speed between the rotating rollers in the collector conveying direction (traveling direction), the Figure 4 The roll film forming device 20 is different from the multi-stage roll film forming. At this time, as described above, by setting the first gap G1, the second gap G2, the third gap G3, and the fourth gap G4 to be gradually reduced in sequence, the wet powder 32 supplied to the film forming unit 40 can appropriately maintain the communicating holes. Although not particularly limited, the size (width) of each gap G1 to G4 can be set within a range of about 10 μm to 100 μm.
[0133] Next, the coating film processing unit 50 of the electrode manufacturing apparatus 70 of this embodiment will be described. Figure 5 As shown, the coating processing unit 50 is a unit for adjusting the properties of the coating 33 imparted on the surface of the collector 31 transmitted from the film forming unit 40. In this embodiment, it has a pressure roller 52 for adjusting the density and film thickness of the coating, and a concave-convex processing roller 54 for forming convexities on the surface of the coating.
[0134] The pressure roller 52 includes a support roller 52B that supports the conveyed collector 31 and is fed in the traveling direction, and a work roller 52A that is arranged at a position opposite to the support roller 52B and is used to press and compress the coating film 33 in the film thickness direction. The pressure roller 52 can press and compress the coating film 33 composed of the wet powder 32 in a pendulum state or a cord state (preferably a cord I state) formed (filmed) on the conveyed collector 31 to an extent that no isolated voids are generated.
[0135] The appropriate pressing pressure by the pressing roller 52 may vary depending on the film thickness and density of the target coating film (electrode active material layer) and is not particularly limited, but can be generally set to about 0.01 MPa to 100 MPa, for example, about 0.1 MPa to 70 MPa.
[0136] The concavoconvex processing roller 54 arranged on the downstream side of the collector conveying direction (travel direction) relative to the pressure roller 52 includes: a support roller 54B that supports the collector 31 conveyed via the pressure roller 52 and is sent out along the travel direction, and a working roller 54A arranged at a position opposite to the support roller 54B and used to squeeze the coating 33 in the film thickness direction to perform concavoconvex formation on the coating surface. That is, the above-mentioned concavoconvex processing roller 54 functions as a second pressure roller, and continuously forms a concavoconvex surface with a predetermined interval (pitch) and pattern on the coating surface by the pressure at this time. Therefore, a corresponding concavoconvex surface for forming a concavoconvex surface with a predetermined interval (pitch) and pattern on the coating surface is formed on the surface of the working roller 54A.
[0137] The appropriate pressing pressure of the above-mentioned convexo-concave processing roller 54 may vary depending on the density of the surface layer of the coating film (electrode active material layer) being the object, the height difference of the concave-convex pattern to be formed (the length between the maximum mountain height and the maximum valley depth, the same below), etc., and is therefore not particularly limited, and can be generally set to 1MPa to 150MPa, for example, about 5MPa to 100MPa.
[0138] In the coating film 33 composed of the wet powder 32 disclosed herein, since interconnected holes reaching the outside are formed therein, compression can be performed without excessive generation of isolated voids. In addition, since it is a coating film with excellent ductility, a concave-convex pattern with a desired height difference can be formed and maintained even in a wet state before drying. Figure 6This is an explanatory diagram schematically showing the content.
[0139] That is, in the case of a coating film formed of a composite material slurry (paste), Figure 6 As shown in (A) in FIG. 1 , it is difficult to form irregularities due to the surface tension of the solvent present on the coating film surface.
[0140] In addition, in the case of a coating film formed from a conventional wet powder in a capillary state, Figure 6 As shown in (B), since the coating film surface contains a large amount of solvent, it is impossible to form irregularities, or even if it is possible, only microscopic irregularities with a small height difference in the irregularity pattern can be formed.
[0141] In addition, when the coating film formed of the composite material slurry (paste) is dried and the dried coating film (i.e., the electrode active material layer) is subjected to concavoconvex formation, as Figure 6 As shown in (D) in the figure, even if a certain degree of unevenness is formed, the surface layer portion where the unevenness is formed will be abnormally dense, or cracks may occur on the surface of the electrode active material layer where the unevenness is formed, or partial detachment (peeling off) may occur, making it very difficult to form sufficient unevenness.
[0142] On the other hand, when the wet powder 32 in the pendulum state or the cord state (preferably the cord I state) disclosed herein is used to form the coating film 33, as Figure 6 As shown in (C), since it is a coating film with excellent ductility, even in a wet state before drying, the coating film surface can be easily formed with unevenness by a pressure roller, and a desired uneven pattern with a height difference can be formed and maintained.
[0143] In the device shown in the figure, only one pair of concavoconvex processing rollers 54 is provided, but the present invention is not limited thereto, and multiple concavoconvex processing rollers may be arranged along the traveling direction and set in a manner that the respective pressing pressures are different. By performing such a multi-stage arrangement, a variety of concavoconvexities with different height differences or patterns can be formed on the surface of the coating film 33 composed of the wet powder 32.
[0144] like Figure 5 As shown, the electrode manufacturing apparatus 70 of this embodiment is provided with a drying chamber 62 equipped with a heater (not shown) as a drying unit 60 on the downstream side of the coating processing unit 50 in the collector conveying direction, and dries the coating 33 on the surface of the collector 31 conveyed from the coating processing unit 50. It should be noted that the drying unit 60 is the same as the drying unit in the conventional electrode manufacturing apparatus, and since it does not particularly characterize the present invention, further detailed description is omitted.
[0145] After the coating film 33 is dried, it is pressed at about 50 to 200 MPa as needed to produce a long sheet electrode for a lithium ion secondary battery. The sheet electrode produced in this way is used as a normal sheet positive electrode or negative electrode to construct a lithium ion secondary battery.
[0146] For example, in Fig.12 2 shows an example of a lithium ion secondary battery 100 that can be constructed using the sheet-shaped electrode of this embodiment.
[0147] The lithium-ion secondary battery (non-aqueous electrolyte secondary battery) 100 of the present embodiment is a battery in which a flat wound electrode body 80 and a non-aqueous electrolyte (not shown) are housed in a battery box (i.e., an outer container) 71. The battery box 71 is composed of a box-shaped (i.e., bottomed rectangular parallelepiped) shell body 72 having an opening at one end (corresponding to the upper end of the battery in the normal use state) and a cover body 74 that seals the opening of the shell body 72. Here, the wound electrode body 80 is housed in the battery box 71 (shell body 72) in a posture in which the winding axis of the wound electrode body is horizontally inverted (i.e., the winding axis of the wound electrode body 80 is almost parallel to the surface direction of the cover body 74). As the material of the battery box 71, for example, a metal material that is lightweight and has good thermal conductivity, such as aluminum, stainless steel, and nickel-plated steel, can be preferably used.
[0148] In addition, if Fig.12 As shown, the cover 74 is provided with a positive terminal 81 and a negative terminal 86 for external connection. The cover 74 is provided with a vent valve 76 set in a manner to release the internal pressure of the battery case 71 when the internal pressure rises to a predetermined level or more, and an injection port (not shown) for injecting a non-aqueous electrolyte into the battery case 71. The battery case 71 can be welded to the periphery of the opening of the battery case main body 72 by welding the cover 74 to the boundary of the battery case main body 72 (sealed).
[0149] The wound electrode body 80 is formed by stacking (overlapping) and winding in the long direction a positive electrode sheet 83 having a positive electrode active material layer 84 formed on one or both sides of a long sheet-like positive electrode collector 82 typically made of aluminum, and a negative electrode sheet 88 having a negative electrode active material layer 89 formed on one or both sides of a long sheet-like negative electrode collector 87 typically made of copper, with two long strips of isolation sheets 90 typically made of porous polyolefin resin between them.
[0150] For the flat-shaped wound electrode body 80, for example, the positive electrode sheet 83, the negative electrode sheet 88 and the long sheet-shaped separator 90 formed with the active material layer composed of the wet powder 32 by the above-mentioned electrode manufacturing device 70 are wound in a cylindrical shape with a perfect circular cross-section, and then the cylindrical winding body is squeezed (pressurized) in a direction orthogonal to the winding axis (typically from the side direction) and flattened, thereby forming it into a flat shape. By making the above-mentioned flat shape, it can be appropriately accommodated in the box-shaped (bottomed rectangular parallelepiped) battery box 71. It should be noted that as the above-mentioned winding method, for example, a method of winding the positive and negative electrodes and the separator around the cylindrical winding axis can be preferably adopted.
[0151] Although not particularly limited, the wound electrode body 80 may be one that is wound in a manner that the positive electrode active material layer non-formed portion 82a (i.e., the portion where the positive electrode collector 82 is exposed without forming the positive electrode active material layer 84) and the negative electrode active material layer non-formed portion 87a (i.e., the portion where the negative electrode collector 87 is exposed without forming the negative electrode active material layer 89) protrude outward from both ends in the winding axial direction. As a result, a winding core in which the positive electrode sheet 83, the negative electrode sheet 88, and the separator 90 are stacked and wound is formed in the central portion of the winding axial direction of the wound electrode body 80. In addition, for the positive electrode sheet 83 and the negative electrode sheet 88, the positive electrode active material layer non-formed portion 82a and the positive terminal 81 (e.g., made of aluminum) may be electrically connected via the positive electrode collector plate 81a, and the negative electrode active material layer non-formed portion 87a and the negative terminal 86 (e.g., made of copper or nickel) may be electrically connected via the negative electrode collector plate 86a. The positive electrode current collector plate 81a, the negative electrode current collector plate 86a, and the positive electrode active material layer non-formed portion 82a, the negative electrode active material layer non-formed portion 87a can be respectively joined by, for example, ultrasonic welding, resistance welding, or the like.
[0152] It should be noted that as a non-aqueous electrolyte, a solution containing an auxiliary salt (supporting salt) in an appropriate non-aqueous solvent (typically an organic solvent) can be typically used. For example, a non-aqueous electrolyte that is liquid at room temperature can be preferably used. As a non-aqueous solvent, various organic solvents used in general non-aqueous electrolyte secondary batteries can be used without particular restrictions. For example, non-protonic solvents such as carbonates, ethers, esters, nitriles, sulfones, and lactones can be used without particular restrictions. As an auxiliary salt, a lithium salt such as LiPF6 can be preferably used. The concentration of the auxiliary salt is not particularly limited, for example, it can be 0.1 to 2 mol / L.
[0153] It should be noted that when implementing the technology disclosed herein, it is not necessary to limit the electrode body to the wound electrode body 80 as shown in the figure. For example, it can also be a lithium-ion secondary battery having a stacked type electrode body formed by stacking a plurality of positive and negative electrode sheets with an isolation member. In addition, according to the technical information disclosed in this specification, it can be seen that the shape of the battery is not limited to the above-mentioned square shape. In addition, although the above-mentioned embodiment is described by taking the non-aqueous electrolyte lithium-ion secondary battery in which the electrolyte is a non-aqueous electrolyte as an example, it is not limited to this. For example, the technology disclosed here can also be applied to the so-called all-solid-state battery that uses a solid electrolyte instead of an electrolyte. In this case, the wet powder in a pendulum state or a cable state is a composition that contains a solid electrolyte as a solid component in addition to the active material.
[0154] The initial charging process is usually performed on a battery assembly that is supplied with a non-aqueous electrolyte and contains an electrode body in a sealed shell. As with the previous lithium-ion secondary batteries of this type, the battery assembly is connected to an external power source between the positive terminal and the negative terminal for external connection, and the initial charging is performed at room temperature (typically around 25°C) until the voltage between the positive and negative terminals reaches a specified value. For example, the initial charging can be performed as follows: starting from charging, charging with a constant current of about 0.1C to 10C until the voltage between the terminals reaches a specified value (for example, 4.3 to 4.8V), followed by constant voltage charging until the SOC (State of Charge) reaches about 60% to 100%, which is constant current constant voltage charging (CC-CV charging).
[0155] Thereafter, a lithium ion secondary battery 100 that can exert good performance can be provided by performing an aging treatment. The aging treatment is performed by keeping the battery 100 after the above-mentioned initial charge in a high temperature region of 35°C or above for 6 hours or more (preferably 10 hours or more, for example 20 hours or more) for high temperature aging. As a result, the stability of the SEI (Solid Electrolyte Interphase) film that can be generated on the surface of the negative electrode during the initial charge can be improved, and the internal resistance can be reduced. In addition, the durability of the lithium ion secondary battery to high temperature storage can be improved. The aging temperature is preferably about 35°C to 85°C (more preferably 40°C to 80°C, and further preferably 50°C to 70°C). When the aging temperature is too lower than the above range, the effect of reducing the initial internal resistance is sometimes not sufficient. When it is too higher than the above range, the non-aqueous solvent and the lithium salt decompose and the electrolyte deteriorates, and sometimes the internal resistance increases. There is no particular upper limit on the aging time, but when it exceeds about 50 hours, the reduction of the initial internal resistance becomes significantly slow, and sometimes the resistance value is almost unchanged. Therefore, from the viewpoint of cost reduction, the aging time is preferably about 6 to 50 hours (more preferably 10 to 40 hours, for example, 20 to 30 hours).
[0156] Several test examples in which the gas-phase controlled wet powder in a pendulum state or a cord state disclosed herein is used as an electrode composite material are described below, but the technology disclosed herein is not intended to be limited to the technical solutions shown in these specific examples.
[0157] <Test Example 1: Production of Negative Electrode>
[0158] A gas-phase controlled wet powder that can be used suitably as a negative electrode composite material is prepared, and then a negative electrode active material layer is formed on a copper foil using the prepared wet powder (negative electrode composite material).
[0159] In this test example, the average particle size (D 50 ) is used as a negative electrode active material, styrene butadiene rubber (SBR) is used as a binder resin, carboxymethyl cellulose (CMC) is used as a thickener, and water is used as a solvent.
[0160] First, a solid component consisting of 95 parts by mass of the above graphite powder, 1 part by mass of CMC and 1 part by mass of SBR was added to a Figure 2 The mixing and stirring treatment is performed in a stirring granulator (planetary mixer, high-speed mixer) having a rotating blade as shown.
[0161] Specifically, the rotation speed of the rotating blade is set to 4500rpm in a stirring granulator with a rotating blade, and a stirring and dispersing process is performed for 15 seconds to obtain a mixture of a powder material composed of the above-mentioned solid components. Water as a solvent is added to the obtained mixture in a manner where the solid component rate is 90% by mass, and a stirring granulation composite process is performed for 30 seconds at a rotation speed of 300rpm, and then, a stirring and micronizing process is continued for 2 seconds at a rotation speed of 1000rpm. Thus, the wet powder (negative electrode composite material) of this test example is prepared.
[0162] The ratio Y / X of the true density Y and the loose bulk density X of the obtained wet powder was calculated and the result was confirmed to be a value greater than 1.2, thereby producing a gas-phase controlled wet powder (negative electrode composite material) in a pendulum state or a cord I state, that is, a gas phase rich in connected pores that are not isolated voids.
[0163] Next, the obtained gas phase controlled wet powder (negative electrode composite material) is supplied to the film forming unit 40 ( Figure 5 ), and transfer the coating film to the surface of a negative electrode collector composed of copper foil prepared separately.
[0164] Afterwards, the negative electrode current collector with the coating is transferred to the coating processing unit, and after being pressed by a pressure roller at a pressure of about 60 MPa, it is heated and dried in a drying unit. Thus, an electrode (negative electrode) having a negative electrode active material layer composed of a gas phase controlled wet powder formed on the negative electrode current collector is obtained.
[0165] The state of the negative electrode active material layer obtained above before drying was observed using SEM.
[0166] It should be noted that, as a comparison object, a conventional wet powder rich in solvent in a capillary state with a ratio Y / X of true density Y to loose bulk density X of about 1.05 was prepared, and coated on a negative electrode collector to form a negative electrode active material layer. The negative electrode active material layer was also observed by SEM before drying. The results are shown in Figures 7A to 8B . Fig. 7A and 7B The surface SEM image and the cross-sectional SEM image respectively show the structure of a negative electrode active material layer formed using a conventional solvent-rich wet powder. Fig. 8A and 8B The surface SEM image and cross-sectional SEM image respectively show the structure of the negative electrode active material layer formed using the vapor-phase controlled wet powder with a Y / X of 1.2 or more.
[0167] according to Fig. 7A and 7B From the SEM image, it can be seen that in the negative electrode active material layer before drying formed by the conventional solvent-rich wet powder, a large amount of solvent (here water) exists between the negative electrode active materials and on the surface of the negative electrode active material layer. Therefore, a reference area represented by Lcm×Bcm (L, B are integers greater than 3) is set on the surface of the negative electrode active material layer and the average surface area measured at n different points (n is an integer greater than 5) is approximately L×B cm 2 It is difficult to form an average surface area of 1.05×L×B cm on the surface of the negative electrode active material layer. 2 The above convex and concave surface.
[0168] On the other hand, according to Fig. 8A and 8B The SEM image shows that in the negative electrode active material layer formed by gas phase controlled wetting powder, there is no excess solvent on the surface of the agglomerated particles constituting the powder. Figure 8BIt is fully demonstrated in the literature that the surface of the negative electrode active material layer formed by gas phase controlled wet powder is composed of fine concave and convex surfaces, and there is no layer composed of solvent covering the entire surface. The fine concave and convex surfaces help to expand the surface area of the active material layer. It is preferred to set a reference area represented by Lcm×Bcm (L, B are integers greater than 3) on the surface of the active material layer and measure the average surface area at n different points (n is an integer greater than 5) to be approximately L×B cm 2 , which can achieve an average surface area of 1.05×L×Bcm 2 above.
[0169] Next, the void structure of the negative electrode active material layer obtained above after being pressurized at 60 MPa (before drying) was investigated by radiation X-ray tomography.
[0170] Radiation X-ray tomography can also be used for test pieces with a thickness of 1.2 mm or less. Since sufficient X-ray transmission intensity can be obtained, the existence form of voids inside the test piece can be observed without destroying the test piece.
[0171] In this example, the Toyota beamline (BL33XU: Toyota Central Research Institute, Ltd.) installed in the large radiation facility "SPring-8" was used for the test. That is, the active material layer test piece whose mass was measured in advance was placed in a cylindrical sample cell equipped with a compression fixture and capable of containing the sample in a state where it can be compressed in the cylindrical direction at a predetermined pressure. The sample cell was arranged on the optical axis between the X-ray emission port and the scintillator.
[0172] Then, an X-ray with an energy of 29 eV is emitted, and an X-ray transmission image of the sample in the sample cell is captured by a CCD camera as a visible light image after conversion to visible light by a scintillator. The above X-ray transmission image (image after conversion to visible light) is captured once every 0.1° while rotating the sample cell containing the sample 360°.
[0173] The 3601 X-ray transmission images (images converted into visible light) thus obtained are reconstructed to obtain a three-dimensional image.
[0174] The void observation results are shown in Fig. 10A and Fig. 10B . Fig. 10A This is the result of the negative electrode active material layer before drying formed from the conventional solvent-rich wet powder. Fig. 10B This is the result of the negative electrode active material layer before drying formed from the above-mentioned gas phase controlled wet powder.
[0175] As shown in the figure, in the negative electrode active material layer formed of the conventional solvent-rich wet powder, no interconnected void paths are observed, and isolated voids (white portions) are scattered.
[0176] On the other hand, in the negative electrode active material layer formed from the gas-phase controlled wet powder disclosed herein after drying, no large isolated voids are observed, and void paths connecting the inside and outside of the active material layer are observed everywhere as a whole.
[0177] The gas residual rate (%) was also measured. Specifically, the gas residual rate (%) was calculated by (volume of air / volume of active material layer immediately before the coating was dried) × 100. Here, the volume of air was calculated by subtracting (mass of solvent / density of solvent), (mass of active material / density of active material), and (solid content / density of solid content) of each solid component contained except the active material from the volume of the coating.
[0178] As a result, Fig. 10A The gas residual rate of the negative electrode active material layer before drying formed from the conventional solvent-rich wet powder shown is about 15%. Fig. 10B The gas residual ratio of the negative electrode active material layer formed of the gas phase controlled wet powder before drying is about 6%.
[0179] This shows that the negative electrode active material layer formed by the previous solvent-rich wet powder has more isolated voids (white parts) because there are no visible connected void paths, so many voids remain inside the active material layer even after pressurization. On the other hand, it shows that the negative electrode active material layer formed by gas-phase controlled wet powder has void paths connecting the inside and outside of the active material layer everywhere on the whole, so the gas residual rate can be greatly reduced by pressurization.
[0180] Next, the three-dimensional image observed by radiation X-ray tomography was analyzed in three dimensions to investigate the distribution of voids. Specifically, assuming that the volume of the sample is consistent with the volume of the internal space of the cylindrical sample cell, the radius of the upper and lower surfaces of the sample cell (R), the distance between the upper and lower surfaces (H), the mass of the sample (M), and the density of the sample when the void ratio is set to 0 (ρ0) were used to calculate the macroscopic void ratio (E) (E = 1-M / (πR 2 Hρ0)).
[0181] In addition, the obtained three-dimensional image is binarized using multiple different thresholds (t1, t2, t3, etc.), the porosity relative to the entire cross-sectional image of the sample is calculated, and the average value (Ev) is obtained. b ) is linearly fitted to the change of void fraction (Ev) (Ev = at b+b, where a and b are fitting parameters), the threshold value (t b ) is used as the binarization threshold in this example.
[0182] The binarized stacked image was read using the famous free image analysis software ImageJFiji, and the plug-in "3D Object Counter" was executed. Then, "Volume" was selected in "Parameters to calculate" and "Objects" was selected in "Maps to show", and the volume of each void considered as a void block and its map (stacked image) were obtained using three-dimensional contact judgment.
[0183] Then, the volume of each void is adjusted to 0-10000 μm 3 The interval is specified and exceeds 10000μm 3 The average volume fraction of each partition when the total volume is set to 1 is calculated. The results are shown in a graph. Fig. 10A and Fig. 10B . Fig. 10A The results of the negative electrode active material layer formed using the conventional solvent-rich wet powder are shown. Fig. 10B The results of the negative electrode active material layer formed by using the gas phase controlled wet powder are shown.
[0184] according to Fig. 10A and Fig. 10B The comparison shows that in the void distribution calculated based on void observation using radiation X-ray tomography, the negative electrode active material layer formed by gas phase controlled wet powder has a void volume of 2000 μm 3 The volume fraction of the above volume is 0.3 or less, that is, 2000 μm with respect to the total void volume (100 vol%). 3 The void ratio of the above volume is 30 vol% or less, which indicates that almost no large isolated voids are formed in the active material layer.
[0185] In contrast, in the negative electrode active material layer formed using the conventional solvent-rich wet powder, it was confirmed that the total void volume was 2000 μm 3 The volume fraction of the above volume exceeds 0.3, that is, 2000 μm relative to the total void volume (100 vol%) 3 The void ratio of the above volume is greater than 30 vol %, which indicates that in the negative electrode active material layer formed using the conventional solvent-rich wet powder, large isolated voids are easily formed due to the excess solvent.
[0186] <Test Example 2: Production of positive electrode>
[0187] A gas-phase controlled wet powder suitable for use as a positive electrode composite material is prepared, and then a positive electrode active material layer is formed on an aluminum foil using the prepared wet powder (positive electrode composite material).
[0188] In this test example, the average particle size (D 50 ) is 20 μm lithium transition metal oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) is used as the positive electrode active material, polyvinylidene fluoride (PVDF) is used as the binder resin, acetylene black is used as the conductive material, and NMP is used as the non-aqueous solvent.
[0189] First, a solid component consisting of 90 parts by mass of the above-mentioned positive electrode active material, 2 parts by mass of PVDF and 8 parts by mass of acetylene black was placed in a Figure 2 The mixing and stirring treatment is performed in a stirring granulator (planetary mixer) having a rotating blade as shown.
[0190] Specifically, the rotation speed of the rotating blade is set to 4500rpm in a stirring granulator with a rotating blade, and a stirring process is performed for 15 seconds to obtain a mixture of a powder material composed of the above-mentioned solid components. NMP as a solvent is added to the obtained mixture in a manner where the solid component rate is 90% by mass or more, and stirring is performed for 30 seconds at a rotation speed of 300rpm, and then, stirring is continued for 2 seconds at a rotation speed of 4500rpm. Thus, the wet powder (positive electrode composite material) of this test example is prepared.
[0191] The ratio Y / X of the true density Y and the loose bulk density X of the obtained wet powder was calculated and confirmed to be a value greater than 1.3, thereby producing a gas-rich gas-controlled wet powder (positive electrode composite material) in a pendulum state or a cord I state, that is, a gas-rich gas-controlled wet powder composed of interconnected pores that are not isolated voids.
[0192] Next, the obtained gas phase controlled wet powder (positive electrode composite material) is fed to the film forming unit 40 ( Figure 5 ) is supplied to transfer the coating film to the surface of a positive electrode current collector composed of aluminum foil prepared separately. In this test example, two similar film forming units are prepared to form coating films on both sides of the positive electrode current collector.
[0193] Thereafter, the positive electrode current collector with the coating is transferred to a coating processing unit, and after being pressed with a pressure roller at a pressure of about 60 MPa, it is heated and dried in a drying unit. Thus, an electrode (positive electrode) having a positive electrode active material layer composed of a gas phase controlled wet powder formed on the positive electrode current collector is obtained.
[0194] The distribution of the binder resin (PVDF) present in the dried positive electrode active material layer thus obtained was investigated by performing conventional SEM-EDX and utilizing fluorine (F) mapping.
[0195] The results are shown in Fig.11 . Fig.11 This is a cross-sectional SEM-EDX image of the positive electrode active material layer used in the F mapping of this test example. The bright spot indicates the location of the F atom (i.e., the location of the PVDF). According to the SEM image, it can be seen that in the positive electrode active material layer made using a positive electrode composite material composed of a gas-phase controlled wet powder, the positive electrode active material layer is evenly divided into two layers, an upper layer and a lower layer, in the thickness direction from the surface of the active material layer to the collector, and the concentration (mg / L) of the binder resin (here PVDF) of the upper and lower layers is set to C1 and C2, respectively, with a relationship of 0.8≤(C1 / C2)≤1.2 (in this test example, the value of C1 / C2 is about 1.1).
Claims
1. A wet powder for forming an electrode active material layer, which is a wet powder for forming an electrode active material layer on an electrode current collector of either a positive electrode or a negative electrode, and is composed of aggregated particles containing a plurality of electrode active material particles, a binder resin and a solvent, At least 50% of the agglomerated particles constituting the wet powder have the following properties: (1) the solid phase, the liquid phase, and the gas phase form a pendulum state or a cord state, the solid phase exists in a state of being connected to each other, and contains the plurality of electrode active material particles and the binder resin as the solid phase, the liquid phase is maintained in a state of bridging between the plurality of electrode active material particles and between the electrode active material particles and the binder resin, and the gas phase forms gaps in the aggregated particles that communicate with the outside, and (2) Under electron microscope observation, no solvent layer is visible on the outer surface of the agglomerated particles, and the solvent fraction is 3 to 8%, achieving the following state: when a coating with a film thickness of 300 μm to 1000 μm is formed on the collector by the wet powder and pressurized at a pressure of 60 MPa, the gas residual rate in the pressurized coating, i.e. (volume of air / volume of coating) × 100, is less than 10 vol%.
2. The wet powder for forming an electrode active material layer according to claim 1, wherein When the bulk density obtained by placing a wet powder of mass g into a container of a predetermined volume mL in a manner of flattening without applying force is measured as loose bulk density X g / mL, and the density calculated from the composition of the wet powder assuming that there is no gas phase is true density Y g / mL, The ratio Y / X of the true density Y to the loose bulk density X is 1.2 or more.
3. The wet powder for forming an electrode active material layer according to claim 1 or 2, wherein: The following state is achieved: in the void distribution obtained by void observation by radiation X-ray tomography of the pressurized coating film, 2000 μm with respect to 100 vol% of the total void volume 3 The void ratio of the above volume is 30 vol% or less.
4. An electrode, which is either a positive electrode or a negative electrode of a secondary battery, comprising an electrode current collector and an electrode active material layer formed on the current collector, The electrode active material layer is formed by using the wet powder for forming the electrode active material layer according to claim 1, The average surface area of the reference region represented by Lcm×Bcm in the electrode active material layer measured at n different points is 1.05×L×Bcm. 2 Above, among them, L and B are integers of 3 or more, and n is an integer of 5 or more.
5. The electrode according to claim 4, wherein The gas residual ratio in the electrode active material layer, that is, (volume of air / volume of coating film)×100, is 10 vol% or less.
6. The electrode according to claim 5, wherein In the void distribution obtained by observing the voids in the electrode active material layer by radiation X-ray tomography, 2000 μm with respect to 100 vol% of the total void volume 3 The void ratio of the above volume is 30 vol% or less.
7. The electrode according to any one of claims 4 to 6, wherein The electrode active material layer is equally divided into two layers, an upper layer and a lower layer, in the thickness direction from the surface of the active material layer to the collector. When the concentrations of the binder resins of the upper layer and the lower layer are set to C1 and C2 respectively, they have a relationship of 0.8≤(C1 / C2)≤1.2, and the unit of the concentration is mg / L.
8. A method for manufacturing an electrode, comprising an electrode current collector and an electrode active material layer having either a positive electrode or a negative electrode, comprising the following steps: A step of preparing a wet powder, wherein the wet powder is composed of aggregated particles including a plurality of electrode active material particles, a binder resin and a solvent, wherein at least 50% of the aggregated particles have the following properties: (1) the solid phase, the liquid phase, and the gas phase form a pendulum state or a cord state, the solid phase exists in a state of being connected to each other, and contains the plurality of electrode active material particles and the binder resin as the solid phase, the liquid phase is maintained in a state of bridging between the plurality of electrode active material particles and between the electrode active material particles and the binder resin, and the gas phase forms voids in the aggregated particles that communicate with the outside, and (2) No solvent layer is visible on the outer surface of the aggregated particles under electron microscope observation, and the solvent fraction is 3 to 8%. in, The following state is achieved: when a coating film with a film thickness of 300 μm to 1000 μm is formed on the collector by the wet powder and pressurized at a pressure of 60 MPa, the gas residual rate in the pressurized coating film, i.e. (volume of air / volume of coating film)×100, is less than 10 vol%; The step of applying the wet powder onto the current collector to form a coating film composed of the wet powder; as well as A step of subjecting the surface of the coating film to a treatment for forming irregularities to form an electrode active material layer having irregularities formed on the surface in a predetermined pattern.
9. The electrode manufacturing method according to claim 8, wherein: The unevenness forming treatment is performed so as to form an uneven surface such that the average surface area of a reference region represented by Lcm×Bcm in the electrode active material layer measured at n different points is 1.05×L×B cm 2 In the above, n is an integer of 5 or more, and L and B are integers of 3 or more.
10. The electrode manufacturing method according to claim 8 or 9, wherein: The coating film forming step is performed by supplying the wet powder between a pair of rotating rollers to form a coating film composed of the wet powder on the surface of one rotating roller, and transferring the coating film onto the surface of the current collector conveyed on the other rotating roller.
11. The electrode manufacturing method according to claim 10, wherein: The unevenness forming treatment is performed by bringing a rotating roller having a predetermined unevenness pattern formed on its surface into contact with the surface of the coating film of the current collector having the coating film.
12. A secondary battery having a positive electrode and a negative electrode. As at least one of the positive and negative electrodes, the electrode according to any one of claims 4 to 7 is provided.
Citation Information
Patent Citations
Manufacturing apparatus of electrode
JP2018037198A
Method for manufacturing electrode
JP2018137087A
Manufacturing method of electrode sheet
JP2019057383A
Method for manufacturing electrode
JP2020136016A
Method of producing negative electrode, negative electrode and lithium-ion secondary battery
CN109755494A